Cone beam computed tomography study of the root canal morphology of maxillary first molars - LIU Hai-xia; MA Yin-zhe (口腔疾病防治, 2016)
Objective To study the value of the application of cone beam CT on the research of root canal morphology of maxillary first molars.Methods Eighty-three maxillary first molars of 70 patients were randomly selected in this study. All teeth were examined for morphology of roots and root canals by cone beam computed tomography (CBCT). The root canals configuration was classified using Vertucci’s classification. The incidence of second mesiobuccal canal (MB2) was calculated.Results All of the maxillary first molars had three separated roots. The incidence of MB2 canal was 38.6%. In the mesiobuccal roots, the most common Vertucci classifications of canal types were type Ⅰ (1-1, 61.4%), type Ⅳ(2-2, 18.1%), typeⅡ(2-1, 15.7%), type Ⅲ(1-2-1, 4.8%).Conclusion The root canal system of maxillary first molars is complicated. CBCT images can facilitate the identification of root canal and provide reference for the root canal treatment.